BRAND REPUTATION ANALYSIS BASED ON BRAND EXPERIENCE VARIABLES AND BRAND POSITIONING CONSISTENCY: A STUDY ON MOTORCYCLE BRANDS IN INDONESIA - Sutisna, Sutisna; Wiguna, Wahyu (Yayasan Education and Social Center, 2025)
Managing brand reputation is a long journey that requires consistency. This study aims to determine how to build a brand reputation based on the influence of brand experience variables and brand positioning consistency. This study is a quantitative study to test the hypothesis. The respondents of this study were Yamaha, Honda and Suzuki motorcycle users. The number of respondents was 414. Data were collected using a questionnaire distributed through social media. The study results showed that brand experience had the most significant influence, with a regression coefficient of 1.619, and its impact was considerable. At the same time, brand positioning consistency was also substantial, with a significant influence of 0.169. The results of the study add managerial insight into building brand reputation.